INSTRUMENTATION AND PROCESS CONTROL ON FLOW AND PRESSURE CONTROL WITH DISTRIBUTED CONTROL SYSTEM (DCS) - FEBRIANO PANGARIBUAN - NIM : 13213043 , WANDIKA
In Honeywell Control System Laboratory Electrical Engineering Major Institut Teknologi Bandung there is a Distributed Control System (DCS) C300 Honeywell and Process Instrumentation Trainer (PIT) FEEDBACK that has not been developed into a closed-loop control system. On PIT, there are sensors and actuators that commonly used for process control. Development of these two modules become close loop control system useful as learning and practical material for instrumentation and process control. Control system that will be develop from these two module are water flow control system and water flow pressure control system. Which is, these two controls system is single input single output (SISO) control system. On every system, DCS have a role as PID controller. DCS also will be connect to computer as interface between operator and control system. Actuator and sensor of control system that will develop is using actuator and sensor that exist on PIT. Every control system is develop with industry standard, which is 4-20mA current and 24V voltage. In the design of the control system, there are specifications to be achieved. Specifications that want to achieve are overshoot, settling time, error steady state, and stability where value of the specifications for the two controls system is different. When designing the system is modeled first. Then, with the model that obtained close loop controls system simulation are performed in MATLAB. PID controller that use is developed with vary method of PID designing that is root-locus, PID Tuner, ZieglerNichols, Direct Synthesis, and Cohen-Coon. When two controls system is tested, they are work corresponding to its specification.